Design and Development of Information System Security with Authentication Using One-Time Password Identification Based on SMS with MD5 Hash - Meiditra, Irzon; Gusti Alex Candra, Dori; Rahmansyah, Rizky; Yuda, Fitra; Restu Selvanda, Alifia (Internet of Things and Artificial Intelligence Journal, 2025)
Login security to access WEB-based applications, in the form of security using OTP (One Time Password) which is generated using Hash MD5 and generates a code sent via SMS. The system will take the email field, password, and phone number. The result of the hash function will produce a 32-digit hexadecimal number. Furthermore, four digits of the hexadecimal number are taken. The four numbers are sent as OTP with Zenziva's Cloud SMS Gateway service and the OTP code will be temporarily stored in the database. The OTP sent to the user will be matched with the one stored in the database table to check its validity. If the OTP sent with the one stored in the table matches, then the user can access the WEB-based application. The OTP generated is for security authentication of the WEB user account after logging in by entering the username and password. Users who enter the wrong OTP 3 times will be blocked, the restriction is to narrow the hackers to intercept and infiltrate.